How to get ideas - Foster, Jack, 1930- (Berrett-Koehler Publishers, 1996)
How to Get Ideas shows you - no matter your age or skill, your job or training - how to come up with more ideas, faster and easier. First, Jack Foster tells you how to condition your mind and become "idea-prone; " how to make the child within you and your sense of humor work for you; how to develop your curiosity, visualize your goals, rethink your thinking, combine different ideas, and overcome your fear of rejection. Then, Foster gives you a five-step procedure for solving problems and getting ideas, a proven procedure that takes the mystery and anxiety out of the idea-generating process, a procedure that works. Learn how easy it is to become more creative. Read the book you're holding.